2018
DOI: 10.1002/aps3.1153
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 19 polymorphic SSR markers in Spirodela polyrhiza (Lemnaceae) and cross‐amplification in Lemna perpusilla

Abstract: Premise of the StudyPolymorphic microsatellite primers were developed for greater duckweed, Spirodela polyrhiza (Lemnaceae), to investigate genetic diversity and structure for application in a bioremediation program.Methods and ResultsA total of 401 publicly available S. polyrhiza whole‐genome shotgun sequences were searched for simple sequence repeat loci of two or more nucleotides. Of these, 60 primer pairs were selected to analyze 68 individuals of S. polyrhiza from three populations. Nineteen polymorphic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…However, this does not allow characterization of all investigated samples at the level of clones. Detection of a larger number of haplo-/genotypes in the species Spirodela polyrhiza and Landoltia punctata was possible by using plastidic inter-simple sequence repeat (ISSR) markers (Xue et al, 2012) or simple sequence repeat (SSR) markers of the plastidic genome (Feng et al, 2017) as well as nuclear SSR markers (Xu et al, 2018). Out of the three studies, the first identified 11 haplotypes of Spirodela polyrhiza and 11 haplotypes of Landoltia punctata in 97 investigated clones, resulting in the specific identification of ca.…”
Section: Delineation Of Speciesmentioning
confidence: 99%
“…However, this does not allow characterization of all investigated samples at the level of clones. Detection of a larger number of haplo-/genotypes in the species Spirodela polyrhiza and Landoltia punctata was possible by using plastidic inter-simple sequence repeat (ISSR) markers (Xue et al, 2012) or simple sequence repeat (SSR) markers of the plastidic genome (Feng et al, 2017) as well as nuclear SSR markers (Xu et al, 2018). Out of the three studies, the first identified 11 haplotypes of Spirodela polyrhiza and 11 haplotypes of Landoltia punctata in 97 investigated clones, resulting in the specific identification of ca.…”
Section: Delineation Of Speciesmentioning
confidence: 99%
“…2018). While some microsatellite markers are known to amplify across more than one duckweed species (Xu et al . 2018), we have not yet explicitly tested these markers against other species.…”
Section: Methodsmentioning
confidence: 99%
“…(2014) developed nine polymorphic and 24 monomorphic haplotype cpDNA-based microsatellite primers for L. minor . Xu et al . (2018) developed 60 microsatellite primers for Spirodela polyrhiza , 19 of which were polymorphic within three populations of S. polyrhiza from China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the characterization of intraspecific genetic variations, i.e., distinct identification of clones within a given species is still at its infant stage [ 27 ]. Most recent efforts in this direction are genotyping clones of S. polyrhiza by sequencing NB-ARC-related genes [ 28 ] and application of genotyping-by-sequencing [ 29 ], or even SSR markers [ 30 , 31 ]. Nevertheless, cross-species amplification for NB-ARC-related genes and Simple sequence repeat (SSR) markers is low within duckweeds [ 28 , 31 ].…”
Section: Introductionmentioning
confidence: 99%